Reinforcement Techniques in Overcoming Post-Power Syndrome Anxiety Disorders in The Elderly - M. Athoiful Fanan; Moh. Ilham; Amriana; Ulfa Aulia Handayani (Proceedings of International Conference on Da'wa and Communication, 2021)
Everyone lives with a variety of presumptions that are not always to their liking, this allows a person to experience tremendous pressure and will foster a prolonged new problem. Post-power syndrome is a phenomenon that occurs in an elderly person who is not ready for old age, motivated by job loss and decreased function of certain organs. Researchers used qualitative research methods through case studies and observations of primary subjects. In this study apply reinforcement work or reinforcement in helping sufferers towards healing, in the form of positive reinforcement on daily good behavior. The results of this study showed that this reinforcement technique has an effect on the healing of post-power syndrome, while involving the participation of the family and the surrounding environment to bring out the meaning in the subject.